Uncovering the Dynamics: Exploring How Organizational Culture and Diversity Shape Organizational Effectiveness - Djunaedi Djunaedi (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2024)
This study aims to investigate the impact of organizational culture and diversity on organizational effectiveness in elementary schools in the XYZ district. Utilizing survey methods and path analysis, the research examines hypotheses regarding the relationships between organizational culture, diversity, and organizational effectiveness. A random sampling process was used to select a sample of 25 elementary schools. The research results show that there is a direct influence of organizational culture on organizational effectiveness, highlighting the importance of building and strengthening cultural values in the school environment. Additionally, there is a direct influence of diversity on organizational effectiveness, emphasizing the importance of managing and utilizing diversity as a positive resource. Research also finds a direct influence of organizational culture on diversity, indicating that a strong organizational culture can shape and influence the dynamics of diversity in elementary schools. These findings provide a deeper understanding of the factors that influence organizational effectiveness at the basic level, as well as provide a foundation for the development of more effective management strategies in improving school performance.